Nurse's duties towards a patient with cancer of the hematopoietic system - Bożena Baczewska; Julita Marciniak; Aleksandra Pawlak; Beata Kropornicka; Ewa Krzyżanowska; Cecylia Olszak; Elżbieta Nowicka; Robert Jan Łuczyk (Kazimierz Wielki University, 2019)
Cancer diseases are among the most common among society. In Poland, more than 100,000 people suffer from cancer of the hematopoietic system. people, and the diagnosis is made to almost six thousand Poles each year. The disease is associated with a long and tiring treatment process, which, like its essence, affects the patient's well-being. The oncology patient spends a large part of his life in the hospital where he is under the care of a medical team. It stands out as a physician, psychologist and nurse, taking care of the patient in a multidimensional and personalized way. Especially between the patient and the nurse, a trust is established, thanks to which the patient has a sense of security and more willingly succumbs to all therapeutic activities performed by him. The aim of this study was to determine the nurse's tasks towards a patient with cancer of the hematopoietic system. The study was conducted using the individual case study method, and the knowledge of the patient's biopsychosocial status was collected on the basis of a patient data sheet, enriched with appropriately selected scales.